Dramaturgi Sakaiba dalam Hibridisasi Budaya Minahasa Sulawesi Utara - Tampake, Tony; Hermanus, Micchelle (Paradigma: Jurnal Kajian Budaya, 2021)
This paper discusses the sakaiba ritual procession in Minahasa which is carried out every year by the Christian community to welcome the New Year. The research was conducted in Taratara village, Tomohon, North Sulawesi. This study focuses on the significance and meaning of the sakaiba ritual procession within the context of the hybridization of contemporary religious culture in Minahasa. By using the theoretical concepts of ritual and dramaturgy, as well as applying the descriptive qualitative methods, this research found that the sakaiba ritual procession is a liminal hinge that allows a peaceful encounter between the ancient Minahasa traditions and the Christian faith. This hinge promotes a contemporary Minahasa religious culture that is inclusive and transformative in the face of other cultural and religious elements present in their history and real life experiences.